Knowledge, Ability and Motivation for the Practice of Checking Mud Content in Sand on Learning Outcomes of Concrete Specifications and Characteristics - Rintowati, Ariani; Suparji, Suparji; Wardhono, Arie; Suhartini, Ratna (Universitas Ahmad Dahlan, 2024)
Sand mining in the area around Sumber Ringin Village, Sri Gading Village, Jati Dukuh Village and around the coast of the Rantas River is a blessing for the people around Mojokerto City and Regency. Mining activities in this area cannot be separated from the attention of many parties and the community, so researchers want to know how much silt content is in the sand and apply it to the basic competencies of concrete specifications and characteristics. This study aims to determine the knowledge, abilities and learning motivation of students in carrying out the practice of silt content in sand on the learning outcomes of basic competency specifications and characteristics of concrete. including research ex post facto. The research design used path analysis. The prerequisite test used is the homogeneity of the F test and the normality test of the Chi Square distribution. Instrument validation was analyzed using the Rasch Model. The research was conducted in class X Modeling Design and Building Information (DPIB) for State Vocational High School (SMK) 1 Mojokerto with a total of 100 students. The results of the research: (1) there is an effect of knowledge on learning outcomes, (2) there is an effect of ability on learning outcomes, (3) there is an effect of knowledge on student learning motivation, (4) there is an influence of ability on student learning motivation, (5) there is an effect of student learning motivation on learning outcomes, (6) there is an influence of knowledge on learning outcomes through learning motivation, (7) there is an effect of ability on learning outcomes through learning motivation.